Analisa Terhadap Tindak Pidana Pemerasan dan Pengancaman Melalui Penyebaran Data Pribadi (Studi Kasus Perkara Nomor 438/Pid.Sus/2020/PN JKT.Utr) (Postulat, 2023)
In the development of technology, there are negative things that arise, one of which is the existence of a criminal act of extortion and/or threats through electronic media as happened in the criminal case with case number 438/Pid.Sus/2020/PN JKT.Utr. In the judge's decision, it was found that the perpetrator was charged with the Criminal Code and the ITE Law which more specifically regulates criminal acts committed through information technology media. This study will discuss the criminal act of Extortion and Threats Through the Dissemination of Personal Data (Analysis of Decision Number 438/Pid.Sus/2020/PN JKT.Utr). The research method used is normative juridical with a case approach. The results of this study are that in making a decision, the judge has legal considerations from the juridical aspect based on the elements of the crime committed by the defendant and also considerations from the non-juridical aspect.